Avaliação do primeiro curso técnico em sistemas de energia renovável do Brasil - Borges Neto, Manuel Rangel (2019)
This thesis describes the experience with the professional training of technicians in the renewable energies (RE) sector. An overview of the public vocational training is presented, followed by a description and evaluation of the experience of implementing the first face-to-face course of technician in ER systems in Brazil. The course was offered in the center of the semi-arid region of northeastern Brazil, which stands out for presenting the country's largest installed capacity in photovoltaic and wind energy generation. The region is characterized by social challenges, such as the lowest Human Development Index among the Brazilian regions. The experiment resulted in the implementation of two face-to-face classes of the Technical Course on ER Systems, concurrently, and a subsequent class at the Federal Institute of Education, Science and Technology of Sertão Pernambucano, in Petrolina - PE. Next, the course performance was verified, from the point of view of technical supervision, teachers, graduates and employers. The main difficulties were raised and, therefore, possible justifications and solutions were presented. Also presented a proposal for a curricular reference matrix and the collaboration of the experiment with the professional and technological education policies of the Ministry of Education.